2013
DOI: 10.1186/1471-2458-13-24
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in overweight and obese children from a large school-based population in Shanghai, China

Abstract: BackgroundThe ongoing rise in the prevalence of hypertension in children and adolescents is considered to be accompanied with the epidemic of childhood overweight and obesity. In this study, we established a large scale cross-sectional study in Shanghai, China, which presented a new evidence for the correlation of hypertension prevalence with overweight and obesity stages in Chinese children and adolescents.MethodsA school-based cross-sectional study was conducted during February to December 2009 in Shanghai, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
0
10

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 16 publications
9
52
0
10
Order By: Relevance
“…A previous study in this city revealed that the prevalence of overweight are increasing among boys and decreasing among girls 14 . Several studies corroborate to our results and have reported tendencies for overweight rates that are higher among male children and adolescents 1,[15][16][17] . In a study conducted in Minas Gerais, the male gender exhibited a 1.86-fold increase in the risk of excess weight 18 .…”
Section: Discussionsupporting
confidence: 92%
“…A previous study in this city revealed that the prevalence of overweight are increasing among boys and decreasing among girls 14 . Several studies corroborate to our results and have reported tendencies for overweight rates that are higher among male children and adolescents 1,[15][16][17] . In a study conducted in Minas Gerais, the male gender exhibited a 1.86-fold increase in the risk of excess weight 18 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, there was a high prevalence of systolic hypertension (22%) and diastolic hypertension (33.8%) among obese children. There was a significant positive correlation of systolic blood pressure in obese children with age, weight, height, BMI as shown in previous studies [11][12][13][14].…”
Section: Resultssupporting
confidence: 76%
“…A study by Lu et al (34) in Shanghai, China showed that the prevalence of diastolic and systolic hypertension is higher among overweight and obese children. In an Indian study by Rao et al (35) 9.7% of school girls had high systolic blood pressure, and blood pressure increased with obesity.…”
Section: Discussionmentioning
confidence: 99%